Bulleyaconitine A prevents Ti particle‐induced osteolysis via suppressing NF‐κB signal pathway during osteoclastogenesis and osteoblastogenesis. Issue 9 (25th March 2018) - Zhang, Liwei; Feng, Mingxuan; Li, Zhiyan; Zhu, Min; Fan, Yongyong; Chu, Binxiang; Yuan, Chiting; Chen, Lihua; Lv, Haiyan; Hong, Zhenghua; Hong, Dun
Abstract : Balanced bone resorption and bone formation are vital for bone homeostasis. Excessive osteoclastic bone resorption in this process can cause a variety of bone disorders including osteoporosis, aseptic prosthetic loosening and tumor associated bone destruction. Bulleyaconitine A (BLA) is a natural compound that has been widely used for pain treatment but its role in osteolysis has not yet been investigated. In this study, we verified for the first time that BLA inhibited osteoclast formation, the mRNA expression of osteoclast‐related genes and osteoclastic bone resorption by inhibiting NF‐κB signal pathway and downstream NFATc1 expression. Meanwhile, BLA had a stimulatory effect in osteoblast differentiation and mineralization. Furthermore, BLA showed preventive effect in Ti particle‐induced osteolysis model in vivo. Together, all our data demonstrated that BLA suppressed osteoclastogenesis and promoted osteoblastogenesis via suppressing NF‐κB signal pathway and could be an alternative therapeutic choice against bone loss. Abstract : Bulleyaconitine A prevents Ti particle‐induced osteolysis by preventing osteoclast formation and promoting osteoblast differentiation.